DNA repair genes polymorphisms and genetic susceptibility to Philadelphia-negative myeloproliferative neoplasms in a Portuguese population: the role of base excision repair genes polymorphisms - Azevedo, Ana P. (2017)
Sob uma licença CC-BY-NC-ND - http://creativecommons.org/licenses/by-nc-nd/4.0/